Exploration de l’évolution des adolescentes victimes d’agression sexuelle participant à des interventions de groupe selon leurs caractéristiques sociofamiliales, leur fonctionnement adaptatif, l’agression subie, son dévoilement et la durée de l’intervention - Geneviève Paquette; Marc Tourigny; Jacques Joly; Isabelle Daigneault (Sociétés et Jeunesses en Difficulté)
Group intervention is a modality very frequently implemented with the adolescent girls who have been sexually abused. These kinds of interventions lead to positive global statistical effects among girls. On the other hand, from an individual clinical point of view, they have a variable effectiveness. The purpose of the study is to verify if some characteristics are associated with their evolution on the effects of the group interventions in which participate the adolescents. The sample consists of 79 adolescents victims of sexual abuse. Hierarchical regressions were used. The results show that the girl’s evolution is associated with some of the studied characteristics for 10 of the 12 effects assessed. These results accentuate the importance of pre-intervention assessment procedures and treatment planning for the adolescents at risk of benefiting less from proposed group interventions. Finally, adjustments are necessary so that group interventions take into account differences between the clinical profiles presented by the participants within the groups.